The Effect of Inflation on Fertility Rates across Regencies and Cities in West Java - Vivie Kartika Yodha; Widimas Faisal; Sutrisno Wibowo (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study examines the macroeconomic determinants of fertility in West Java, Indonesia, with particular emphasis on the role of inflation in shaping the trajectory of the regional fertility rate. Using an unbalanced panel dataset of 27 kabupaten/kota (regencies and cities) over the period 2016 to 2023, this study employs the panel Fixed Effect estimator to quantify the extent to which inflation influences the total fertility rate and the crude birth rate. The empirical results consistently demonstrate a negative and statistically significant association between the Consumer Price Index and fertility rate. The negative effect of inflation on fertility is concentrated in the Metro region of Greater Jakarta's periphery, where the cost of living pressure is most acute. Further analysis reveals that the adverse effect of inflation on fertility is amplified over the long run, implying that persistent price level increases translate into sustained downward pressure on reproductive decisions. The results remain robust when the crude birth rate is used as an alternative measure of fertility and when the bias-corrected Least Squares Dummy Variables estimator is applied as a robustness check. This study contributes to the emerging literature on the macroeconomic determinants of fertility in middle-income developing regions by providing new district-level evidence from Indonesia's most populous province and by underscoring the long-run implications of sustained inflationary pressure on fertility outcomes. Several policy measures are proposed, including the expansion of the Program Keluarga Harapan conditional cash transfer to include a dedicated child benefit component, the extension of the childcare subsidy under Kartu Prakerja to female workers in informal sectors, and the acceleration of the Tapera housing savings program to reduce household financial burdens associated with family formation.